Effect of plant age on in-soil decomposition and nitrogen content of sunn hemp tissue. Issue 21 (30th November 2018) - Baitsaid, A.; Schaffer, B.; Vargas, A.I.; Li, Y.; Liu, G.
ABSTRACT: The effects of plant age at the time of mowing on sunn hemp ( Crotalaria juncea L.) tissue decomposition, nitrogen (N) release, and fiber content in Krome very gravelly loam were assessed. Combined leaf and stem tissue from 42-, 77- or 112-day-old sunn hemp plants was placed in mesh bags and buried below the soil surface in the field. Bags were removed bi-weekly and dry weights, N concentration, acid detergent fiber (ADF) and neutral detergent fiber (NDF) concentrations in buried sunn hemp tissues were determined. There was a rapid decrease plant tissue dry weight during the first 14 days after tissue was buried, followed by a slow gradual decrease. The amount N per hectare was much lower for 42-day-old than 112-day-old sunn hemp. Tissue of the youngest plants decomposed the quickest. Forty two-day-old tissue had a higher N concentration, N mineralization rate, and lower NDF and ADF than 77- or 112-day-old tissue. Mowing and soil incorporation of a 42-day-old instead of a 77- to 112-day-old sunn hemp cover crop prior to planting a cash crop can be beneficial for a fast-growing cash crop planted soon after soil incorporation of the cover crop.